Arithmetic version of boolean algebra - Azram, Mohammad; Daoud, Jamal Ibrahim; Mohamed Elfaki, Faiz Ahmed (2009)
In this article we will discuss that the logical results in Boolean algebra can equally be derived with ordinary algebraic operations. We will establish arithmetic versions of the common logical propositions inclusive of Sheffer stroke (Nand connective) and Peirce’s arrow (Nor connective) which are very important to design circuit diagrams. We will present the comparison of some basic logical Boolean expressions and their arithmetic version through the truth tables. Finally we will establish the fundamental logical equivalent propositions via arithmetic versions.